Correlation analysis of HbA1c versus random, fasting, and postprandial glucose levels as predictors of glycemic control in type 2 diabetes patients - Ansari, Shiba; Jayeeta Bhadra; Ahirwar, Ashok Kumar; Gupta, Jasmeen (Asian Journal of Medical Sciences, 2023)
Background: Glycated Hemoglobin (HbA1c) is used for assessing glycemic control over the past 8–12 weeks. This is critical for determining the efficacy of diabetes treatment and predicting the progression of microvascular complications. However, in health-care situations where tests for HbA1c are either unavailable or unfeasible for any reason, clinicians rely only on plasma glucose values for assessing the glycemic control of the patient. Aims and Objectives: The purpose of this study was to determine the relationship between HbA1c and fasting, postprandial, and random plasma glucose levels. Materials and Methods: Routine blood samples obtained from the laboratory to measure HbA1c and plasma glucose (fasting/postprandial/random) were used for study. A total of 207 samples were used to investigate the relationship between HbA1c and fasting and postprandial glucose (PPG/PP). The correlation of HbA1c with random glucose values was investigated using 112 samples. HbA1c was estimated by immunoturbidimetry and glucose was estimated by hexokinase method. Pearson’s correlation analysis was done by SPSS version 20 software. Results: The Pearson correlation coefficient (r) with regard to PPG/PP and HbA1c was 0.75 (P=0.01, 95% CI), fasting glucose and HbA1c was 0.73 (P=0.01, 95% CI), and random glucose and HbA1c was 0.59 (P=0.01, 95% CI). Conclusion: PPG/PP correlates with HbA1c better than fasting or random glucose. When it is impossible to perform HbA1c measurements, PPG measurements should be used instead.